Optimalisasi Pengelolaan Bisnis Retail Minimarket Sugimart - Rini Rahayu Kurniati; A . Ramadlan (Akutansi Bisnis & Manajemen ( ABM ), 2015)
The purpose of "Sunan Giri" orphanage is tackling adolescent delinquency in order to be the generation that possessed akhlakul karimah, capable and skilled for the sake of theirs future. "Sunan Giri" orphanage attempt to contribute in Indonesia development by conducting retail minimarket that called "Sugimart". Changes and developments in the retail market also requires offenders to change the old paradigm of traditional retail management towards modern retail management paradigm (Utami, 2006). The aims of this research are: (1) Explain the retail business management minimarket "Sugimart" conducted by "Sunan Giri" orphanage Jetis Malang, (2) Explain the problem, (3) Explain the management optimization. This research use descriptive qualitative method. The results show that management is not optimal. According to the results of the interview due to: the employees who do not have the experience need to be trained, leadership skills that managers still less so the impact on all management including the arrangement of working hours are less disciplined in carrying out the work shift. Capital is still weak; the competition minimarket is also very competitive and very tight with popping Indomaret, Alfamart and others, so that the development of mini-market Sugimart retail looks to no avail.